The Hazards of a Practicing Respirologist - Dennis Bowie (Canadian Respiratory Journal)
The advent of severe acute respiratory syndrome (SARS) in March 2003 reminded us that health care workers are at risk of being stricken with the very diseases that we are treating. Health care workers accounted for 65% of the SARS cases in Canada (1) and represented at least one-quarter of the cases in Hong Kong (2). Because SARS presents as a severe pneumonia and is diagnosed by certain epidemiological characteristics, history and a positive chest x-ray, respirologists are often the first-line consultants to see patients with an unusual pneumonia. If we are lucky, there may be telling clues to the diagnosis such as a travel history or contact with other cases. However, in the absence of these clues, it behooves the medical profession to use universal precautions.